2006
DOI: 10.1118/1.2198198
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of entrance exposure and signal-to-noise ratio between an SBDX prototype and a wide-beam cardiac angiographic system

Abstract: The scanning-beam digital x-ray (SBDX) system uses an inverse geometry, narrow x-ray beam, and a 2-mm thick CdTe detector to improve the dose efficiency of the coronary angiographic procedure. Entrance exposure and large-area iodine signal-to-noise ratio (SNR) were measured with the SBDX prototype and compared to that of a clinical cardiac interventional system with image intensifier (II) and charge coupled device (CCD) camera (Philips H5000, MRC-200 x-ray tube, 72 kWp max). Phantoms were 18.6-35.0 cm acrylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 20 publications
1
44
0
Order By: Relevance
“…Narrow beam scanning drastically reduces image scatter levels relative to conventional fluoroscopy, which in turn allows a desired image quality to be obtained with fewer primary x-rays and lower patient dose. 24 Entrance dose is further reduced because x-rays are spread over a larger area at the patient entrance, compared to conventional cone beam imaging. This study also indicates that significant integral dose reduction could be obtained in the case of single object tracking, by modifying the active portion of the scan pattern so that only the area around the object is illuminated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Narrow beam scanning drastically reduces image scatter levels relative to conventional fluoroscopy, which in turn allows a desired image quality to be obtained with fewer primary x-rays and lower patient dose. 24 Entrance dose is further reduced because x-rays are spread over a larger area at the patient entrance, compared to conventional cone beam imaging. This study also indicates that significant integral dose reduction could be obtained in the case of single object tracking, by modifying the active portion of the scan pattern so that only the area around the object is illuminated.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 The x-ray source has a focal spot that is rasterscanned over an array of positions on a transmission-style target [ Fig. 1(a)].…”
Section: Iia Imaging System and Tracking Algorithmmentioning
confidence: 99%
“…An extended discussion on the method and the imaging performance has been published, [17][18][19] and here we highlight only some of the unique features of the SBDX technology. Refer to Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that radiation dose can be significantly reduced in adult cardiac procedures by using our scanning beam digital x-ray (SBDX) system 4 --a fluoroscopic imaging system that employs an inverse imaging geometry 5,6 ( Figure 1, Movie 1 and Figure 2). Instead of a single focal spot and an extended detector as used in conventional systems, our approach utilizes an extended X-ray source with multiple focal spots focused on a small detector.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatrics procedures are in general much more complex than those performed on adults and thus are on average four to eight times longer 1 . Furthermore, children can undergo up to 10 fluoroscopic procedures by the age of 10, and have been shown to have a three-fold higher risk of developing fatal cancer throughout their life than the general population 2,3 .We have shown that radiation dose can be significantly reduced in adult cardiac procedures by using our scanning beam digital x-ray (SBDX) system 4 --a fluoroscopic imaging system that employs an inverse imaging geometry 5,6 ( Figure 1, Movie 1 and Figure 2). Instead of a single focal spot and an extended detector as used in conventional systems, our approach utilizes an extended X-ray source with multiple focal spots focused on a small detector.…”
mentioning
confidence: 99%